PERLINDUNGAN HUKUM TERHADAP PENANAMAN MODAL PADA BIDANG USAHA MINERAL DAN BATU BARA DI INDONESIA - Herdandi Irsyad Bhagaskara (2022)
Economic growth is one of the important things of a country, good economic growth can be an indicator that it can stand alone and meet its financial needs independently. One of them is the Mineral and Coal Business which has great potential to improve the welfare of the people.However, the potential for capital investment is still lacking due to fears from investors regarding the legal protection provided. The method used by the author is Yuridis Normative, which has the purpose of knowing the legal protection of foreign and domestic investment and to determine the factors that hinder foreign and domestic investment in the field of Minerals and Coal in Indonesia.This is the subject of legal protection following the revision of Law No. 3 of 2020 of Minerals and Coal and Law No. 11 of 2020 on Job Creation where there are still many problems regarding legal protection i.e. First, regulatory inconsistencies and the rapid change of regulations. Second, conflicts between mining regulations and forestry regulations. Third, law enforcement officials cannot stop anarchism, Fourth, there needs to be a mining agreement similar to the labor contract system in the new mining law; Fifth, unfairness in divestment of foreign ownership and closure of mines.